Physician Utilization of a Hospital Information System: A Computer Simulation Model - Anderson, James G. (1988)
The purpose of this research was to develop a computer simulation model that represents the process through which physicians enter orders into a hospital information system (HIS). Computer simulation experiments were performed to estimate the effects of two methods of order entry on outcome variables. The results of the computer simulation experiments were used to perform a cost-benefit analysis to compare the two different means of entering medical orders into the HIS. The results indicate that the use of personal order sets to enter orders into the HIS will result in a significant reduction in manpower, salaries and fringe benefits, and errors in order entry.